Improved Outcomes and Value in Staged Hybrid Extent II Thoracoabdominal Aortic Aneurysm Repair - Hawkins, Robert B. (J Vasc Surg, 2017)
OBJECTIVE: Complex Crawford extent II thoracoabdominal aortic aneurysms (TAAA) can be treated in a hybrid manner with proximal thoracic endovascular aneurysm repair, followed by staged distal open thoracoabdominal repair. The purpose of this study was to evaluate the outcomes and healthcare associated value of this new method compared to traditional open repair over 10 years. METHODS: A prospectively collected database was used to identify all patients with extent II TAAA undergoing repair at a single institution between 2005 and 2015. Patient characteristics, post-operative outcomes, and incidence of major adverse events (MAE = renal failure, spinal cord ischemia, death) were compared. After adjusting for time since surgery, value was analyzed looking at quality (1/MAE) divided by cost (total health system cost). This is multiplied by a constant to set the value of open TAAA repair to 100. RESULTS: A total of 113 consecutive patients underwent extent II TAAA repairs, of which 25 (22.1%) had a staged hybrid approach with a median of 129 days between procedures. No baseline differences in demographic or comorbidity variables existed between groups (p>0.05). The hybrid group had shorter operative time (255 vs 306 minutes; p=0.01), shorter postoperative length of stay (LOS) (10.1 vs 13.3 days; p=0.02), as well as reduced blood loss (1300 vs 2600 mL; p=0.01) at the time of open operation. Despite higher rates of acute kidney injury in the hybrid group (76.0%vs 51.1%, p=0.03) there was no difference in renal failure (8.0% vs 4.5%, p=0.84) The incidence of MAE was lower in the staged hybrid group (20.0% vs 48.9%; p=0.01), without a difference in hospital mortality (4.0 vs 3.4%, p=0.89). Median total cost was higher in the hybrid group ($112,920 vs $72,037, p=0.003). Value was improved in the hybrid group by 56% using mean cost and 178% by median cost. CONCLUSIONS: The 20% major adverse event rate associated with staged hybrid repair of extent II TAAA was significantly decreased compared to open repair, with a relative reduction of over 50%. Despite higher total hospital costs, staged hybrid repair had 56% to 178% higher healthcare related value compared to standard open repair. In an era of increasing focus on costs and quality, staged hybrid repair of extensive TAAAs is associated with fewer complications than open TAAA repair resulting in a good value investment from a resource utilization perspective.